An assessment of contaminants and benthic condition in the Matagorda Bay system (Texas, USA) - Jasmine J. Caillier; Paul A. Montagna; Marie E. DeLorenzo; Katy W. Chung; Peter B. Key (Environmental Science and Pollution Research, 2026)
The Matagorda Bay system has suffered a long-term decline in benthic abundance, biomass, and diversity since the 1980’s. This study examined sediment contamination to determine if legacy pollutants are degrading sediment quality and are a possible cause for ecosystem degradation. Degradation can be indicated by a decline in benthic integrity (i.e., diversity), decreased survival rates of organisms exposed to sediment, and sediment chemical contaminant concentrations over threshold limits. These methods form the Sediment Quality Triad to assess environmental effects. There were no contaminant concentrations above threshold limits for PCBs or DDTs, but 46% of 24 stations had concentrations over threshold limits, established by sediment quality guidelines, for seven trace elements and one PAH: arsenic (As), cadmium (Cd), mercury (Hg), copper (Cu), lead (Pb), nickel (Ni), and silver (Ag); and dibenzo (a,h) anthracene. Mostly near river mouths, 16 of the 24 stations had moderate to high toxicity, and 17 out of the 24 stations had fair to low diversity. Toxicity was inversely correlated with diversity, but there were no correlations between sediment chemistry and toxicity or benthic metrics. These findings indicate that legacy chemical contamination is not driving estuary-wide degradation of benthic communities The only station where high contamination was linked to high toxicity and low diversity was in the uppermost region of Lavaca Bay close to creek mouths. Low diversity and/or high toxicity was common near river and creek mouths. Because unmeasured pollution could be entering from rivers and creeks, management plans for the watershed and non-point sources could help to protect this ecosystem.

Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

Positive feedbacks among biotic and abiotic stressors mediate whitebark pine decline - Sara J. Germain; Matthew F. Bekker; Savannah A. Collins-Key; Georg von Arx (Forest Ecology and Management, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Effects of Vibrio vulnificus and Microcystis aeruginosa co-exposures on microplastic accumulation and depuration in the Eastern Oyster (Crassostrea virginica) - Jessica T. Wenclawiak; John E. Weinstein; Peter B. Key; Craig J. Plante; Barbara A. Beckingham (Environmental Pollution, 2024)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Siderophore production and utilization by marine bacteria in the North Pacific Ocean - Jiwoon Park; Bryndan P. Durham; Rebecca S. Key; Ryan D. Groussman; Zinka Bartolek; Paulina Pinedo‐Gonzalez; Nicholas J. Hawco; Seth G. John; Michael C. G. Carlson; Debbie Lindell; Lauren W. Juranek; Sara Ferrón; et al. (Limnology and Oceanography, 2023)
Siderophores are strong iron‐binding molecules produced and utilized by microbes to acquire the limiting nutrient iron (Fe) from their surroundings. Despite their importance as a component of the iron‐binding ligand pool in seawater, data on the distribution of siderophores and the microbes that use them are limited. Here, we measured the concentrations and types of dissolved siderophores during two cruises in April 2016 and June 2017 that transited from the iron‐replete, low‐macronutrient North Pacific Subtropical Gyre through the North Pacific Transition Zone (NPTZ) to the iron‐deplete, high‐macronutrient North Pacific Subarctic Frontal Zone (SAFZ). Surface siderophore concentrations in 2017 were higher in the NPTZ (4.0–13.9 pM) than the SAFZ (1.2–5.1 pM), which may be partly attributed to stimulated siderophore production by environmental factors such as dust‐derived iron concentrations (up to 0.51 nM). Multiple types of siderophores were identified on both cruises, including ferrioxamines, amphibactins, and iron‐free forms of photoreactive siderophores, which suggest active production and use of diverse siderophores across latitude and depth. Siderophore biosynthesis and uptake genes and transcripts were widespread across latitude, and higher abundances of these genes and transcripts at higher latitudes may reflect active siderophore‐mediated iron uptake by the local bacterial community across the North Pacific. The variability in the taxonomic composition of bacterial communities that transcribe putative ferrioxamine, amphibactin, and salmochelin transporter genes at different latitudes further suggests that the microbial groups involved in active siderophore production and usage change depending on local conditions.

Homo floresiensis and Homo luzonensis are not temporally exceptional relative to Homo erectus - David L. Roberts; Ivan Jarić; Stephen J. Lycett; Dylan Flicker; Alastair Key (Journal of Quaternary Science, 2023)
The presence of Homo floresiensis and Homo luzonensis in southeast Asia 90,000 to 60,000 years ago is considered surprising by many, and has been used to support their designation as unique species and the islands they were discovered on as refugia. Here, we statistically test the null hypothesis that H. floresiensis and H . luzonensis represent temporally uninterrupted occurrences relative to Homo erectus . We do this using the ‘surprise test’ for the exceptionality of a new record. Results demonstrate that H. floresiensis and H. luzonensis are not temporally distinct relative to H. erectus . Their late persistence should, therefore, not be considered surprising, they cannot reliably be inferred to be outside of H. erectus ’ temporal range, and – temporally – the islands of Luzon and Flores are not supported as refugia. Similarly, late H. erectus at Ngandong, Java, is not demonstrated to be temporally distinct relative to earlier, principally mainland‐Asian, H. erectus . Further, we demonstrate that substantial numbers of fossil discoveries would be needed before H. floresiensis and H. luzonensis are outside of H. erectus’ expected temporal range. If H. floresiensis and H. luzonensis are descended from H. erectus populations, our results point toward either geographic processes of allopatric speciation or behavioural processes leading to a sympatric speciation event.

Bacterial species diversity of traditionally ripened sheep legs from the Faroe Islands (skerpikjøt) - Christina Charmpi; Kristian Key Milan Thamsborg; Svein-Ole Mikalsen; Eyðfinn Magnussen; Ana Sosa Fajardo; David Van der Veken; Jørgen J. Leisner; Frédéric Leroy (International Journal of Food Microbiology, 2023)

Meat consumption and risk of ischemic heart disease: A systematic review and meta-analysis - Keren Papier; Anika Knuppel; Nandana Syam; Susan A. Jebb; Tim J. Key (Critical Reviews in Food Science and Nutrition, 2023)

Physical activity in relation to circulating hormone concentrations in 117,100 men in UK Biobank - Eleanor L. Watts; Aurora Perez-Cornago; Aiden Doherty; Naomi E. Allen; Georgina K. Fensom; Sandar Tin Tin; Timothy J. Key; Ruth C. Travis (Cancer Causes & Control, 2021)
Purpose Physical activity may reduce the risk of some types of cancer in men. Biological mechanisms may involve changes in hormone concentrations; however, this relationship is not well established. Therefore, we aimed to investigate the associations of physical activity with circulating insulin-like growth factor-I (IGF-I), sex hormone-binding globulin (SHBG, which modifies sex hormone activity), and total and free testosterone concentrations, and the extent these associations might be mediated by body mass index (BMI). Methods Circulating concentrations of these hormones and anthropometric measurements and self-reported physical activity data were available for 117,100 healthy male UK Biobank participants at recruitment. Objectively measured accelerometer physical activity levels were also collected on average 5.7 years after recruitment in 28,000 men. Geometric means of hormone concentrations were estimated using multivariable-adjusted analysis of variance, with and without adjustment for BMI. Results The associations between physical activity and hormones were modest and similar for objectively measured (accelerometer) and self-reported physical activity. Compared to men with the lowest objectively measured physical activity, men with high physical activity levels had 14% and 8% higher concentrations of SHBG and total testosterone, respectively, and these differences were attenuated to 6% and 3% following adjustment for BMI. Conclusion Our results suggest that the associations of physical activity with the hormones investigated are, at most, modest; and following adjustment for BMI, the small associations with SHBG and total testosterone were largely attenuated. Therefore, it is unlikely that changes in these circulating hormones explain the associations of physical activity with risk of cancer either independently or via BMI.

Kinematic and Somatosensory Gains in Infants with Cerebral Palsy After a Multi-Component Upper-Extremity Intervention: A Randomized Controlled Trial - Nathalie L. Maitre; Arnaud Jeanvoine; Paul J. Yoder; Alexandra P. Key; James C. Slaughter; Helen Carey; Amy Needham; Micah M. Murray; Jill Heathcock; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; et al. (Brain Topography, 2020)

Mapping the effectiveness of nature‐based solutions for climate change adaptation - Alexandre Chausson; Beth Turner; Dan Seddon; Nicole Chabaneix; Cécile A. J. Girardin; Valerie Kapos; Isabel Key; Dilys Roe; Alison Smith; Stephen Woroniecki; Nathalie Seddon (Global Change Biology, 2020)
Nature‐based solutions (NbS) to climate change currently have considerable political traction. However, national intentions to deploy NbS have yet to be fully translated into evidence‐based targets and action on the ground. To enable NbS policy and practice to be better informed by science, we produced the first global systematic map of evidence on the effectiveness of nature‐based interventions for addressing the impacts of climate change and hydrometeorological hazards on people. Most of the interventions in natural or semi‐natural ecosystems were reported to have ameliorated adverse climate impacts. Conversely, interventions involving created ecosystems (e.g., afforestation) were associated with trade‐offs; such studies primarily reported reduced soil erosion or increased vegetation cover but lower water availability, although this evidence was geographically restricted. Overall, studies reported more synergies than trade‐offs between reduced climate impacts and broader ecological, social, and climate change mitigation outcomes. In addition, nature‐based interventions were most often shown to be as effective or more so than alternative interventions for addressing climate impacts. However, there were substantial gaps in the evidence base. Notably, there were few studies of the cost‐effectiveness of interventions compared to alternatives and few integrated assessments considering broader social and ecological outcomes. There was also a bias in evidence toward the Global North, despite communities in the Global South being generally more vulnerable to climate impacts. To build resilience to climate change worldwide, it is imperative that we protect and harness the benefits that nature can provide, which can only be done effectively if informed by a strengthened evidence base.

Uptake and Biological Effects of Perfluorooctane Sulfonate Exposure in the Adult Eastern Oyster Crassostrea virginica - Allisan A. Aquilina-Beck; Jessica L. Reiner; Katy W. Chung; Meaghan J. DeLise; Peter B. Key; Marie E. DeLorenzo (Archives of Environmental Contamination and Toxicology, 2020)

Neonatal Multisensory Processing in Preterm and Term Infants Predicts Sensory Reactivity and Internalizing Tendencies in Early Childhood - Nathalie L. Maitre; Alexandra P. Key; James C. Slaughter; Paul J. Yoder; Mary Lauren Neel; Céline Richard; Mark T. Wallace; Micah M. Murray (Brain Topography, 2020)
Multisensory processes include the capacity to combine information from the different senses, often improving stimulus representations and behavior. The extent to which multisensory processes are an innate capacity or instead require experience with environmental stimuli remains debated. We addressed this knowledge gap by studying multisensory processes in prematurely born and full-term infants. We recorded 128-channel event-related potentials (ERPs) from a cohort of 55 full-term and 61 preterm neonates (at an equivalent gestational age) in response to auditory, somatosensory, and combined auditory-somatosensory multisensory stimuli. Data were analyzed within an electrical neuroimaging framework, involving unsupervised topographic clustering of the ERP data. Multisensory processing in full-term infants was characterized by a simple linear summation of responses to auditory and somatosensory stimuli alone, which furthermore shared common ERP topographic features. We refer to the ERP topography observed in full-term infants as “typical infantile processing” (TIP). In stark contrast, preterm infants exhibited non-linear responses and topographies less-often characterized by TIP; there were distinct patterns of ERP topographies to multisensory and summed unisensory conditions. We further observed that the better TIP characterized an infant’s ERPs, independently of prematurity, the more typical was the score on the Infant/Toddler Sensory Profile (ITSP) at 12 months of age and the less likely was the child to the show internalizing tendencies at 24 months of age. Collectively, these results highlight striking differences in the brain’s responses to multisensory stimuli in children born prematurely; differences that relate to later sensory and internalizing functions.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

An Historical Geoarchaeological Approach to Sourcing an Eighteenth Century Building Stone: Use of Aquia Creek Sandstone in Christ Church, Lancaster County, VA, USA - Marcus M. Key; Spencer B. Lieber; Robert J. Teagle (Geoheritage, 2020)

Investigating interrelationships between Lower Palaeolithic stone tool effectiveness and tool user biometric variation: implications for technological and evolutionary changes - Alastair J.M. Key; Stephen J. Lycett (Archaeological and Anthropological Sciences, 2018)

Comparative Toxicity of Two Chemical Dispersants and Dispersed Oil in Estuarine Organisms - M. E. DeLorenzo; P. B. Key; K. W. Chung; E. Pisarski; B. Shaddrix; E. F. Wirth; P. L. Pennington; J. Wade; M. Franco; M. H. Fulton (Archives of Environmental Contamination and Toxicology, 2018)

Reassessing the production of handaxes versus flakes from a functional perspective - Alastair J.M. Key; Stephen J. Lycett (Archaeological and Anthropological Sciences, 2017)

Somatosensory Event-Related Potentials and Association with Tactile Behavioral Responsiveness Patterns in Children with ASD - Carissa J. Cascio; Chang Gu; Kimberly B. Schauder; Alexandra P. Key; Paul Yoder (Brain Topography, 2015)

Dietary greenhouse gas emissions of meat-eaters, fish-eaters, vegetarians and vegans in the UK - Peter Scarborough; Paul N. Appleby; Anja Mizdrak; Adam D. M. Briggs; Ruth C. Travis; Kathryn E. Bradbury; Timothy J. Key (Climatic Change, 2014)

Relationship between land use classification and grass shrimp Palaemonetes spp. population metrics in coastal watersheds - James W. Daugomah; P. B. Key; J. B. West; N. R. Shea; S. McDaniel; P. L. Pennington; M. H. Fulton (Environmental Monitoring and Assessment, 2014)

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Anthropometric characteristics and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Fatemeh Saberi Hosnijeh; Isabelle Romieu; Valentina Gallo; Elio Riboli; Anne Tjønneland; Jytte Halkjær; Guy Fagherazzi; Françoise Clavel-Chapelon; Laure Dossus; Annie Lukanova; Rudolf Kaaks; Antonia Trichopoulou; et al. (Cancer Causes & Control, 2013)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Recent range expansions in non-native predatory beetles on sub-Antarctic South Georgia - P. Convey; R. S. Key; R. J. D. Key; M. Belchier; C. L. Waller (Polar Biology, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Prospective study of physical activity and risk of primary adenocarcinomas of the oesophagus and stomach in the EPIC (European Prospective Investigation into Cancer and nutrition) cohort - José María Huerta; Carmen Navarro; María-Dolores Chirlaque; María-José Tormo; Karen Steindorf; Genevieve Buckland; Fátima Carneiro; Nina Føns Johnsen; Kim Overvad; Jakob Stegger; Anne Tjønneland; Marie-Christine Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Effects of chemically spiked sediments on estuarine benthic communities: a controlled mesocosm study - W. L. Balthis; J. L. Hyland; M. H. Fulton; P. L. Pennington; C. Cooksey; P. B. Key; M. E. DeLorenzo; E. F. Wirth (Environmental Monitoring and Assessment, 2010)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Prospective study of the association between grapefruit intake and risk of breast cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Carla H. van Gils; Anja Olsen; Anne Tjønneland; Françoise Clavel-Chapelon; Marie-Christine Boutron-Ruault; Marina Touillaud; Maria-José Sánchez; Sheila Bingham; Kay Tee Khaw; et al. (Cancer Causes & Control, 2009)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Direct inoculation of RNA transcripts from an infectious cDNA clone of porcine reproductive and respiratory syndrome virus (PRRSV) into the lymph nodes and tonsils of pigs initiates PRRSV infection in vivo - K. F. Key; J. DiCristina; J. Gillespie; D. K. Guenette; X. J. Meng (Archives of Virology, 2007)

Fruit and vegetable consumption and lymphoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Sabine Rohrmann; Nikolaus Becker; Jakob Linseisen; Alexandra Nieters; Thomas Rüdiger; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Rudolf Kaaks; Manuela M. Bergmann; Heiner Boeing; et al. (Cancer Causes & Control, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

An evaluation of contaminated estuarine sites using sediment quality guidelines and ecological assessment methodologies - M. Fulton; P. Key; E. Wirth; A. K. Leight; J. Daugomah; D. Bearden; S. Sivertsen; G. Scott (Ecotoxicology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

Intake of fruits and vegetables and risk of cancer of the upper aero-digestive tract: the prospective EPIC-study - Heiner Boeing; Thomas Dietrich; Kurt Hoffmann; Tobias Pischon; Pietro Ferrari; Petra H. Lahmann; Marie Christine Boutron-Ruault; Francoise Clavel-Chapelon; Naomi Allen; Tim Key; Guri Skeie; Eiliv Lund; et al. (Cancer Causes & Control, 2006)

A prospective study of diet and prostate cancer in Japanese men - Naomi E. Allen; Catherine Sauvaget; Andrew W. Roddam; Paul Appleby; Jun Nagano; Gen Suzuki; Timothy J. Key; Kojiro Koyama (Cancer Causes & Control, 2004)

Surface Water Pesticide Movement from the Dade County Agricultural Area to the Everglades and Florida Bay via the C-111 Canal - M. H. Fulton; G. I. Scott; M. E. DeLorenzo; P. B. Key; D. W. Bearden; E. D. Strozier; C. J. Madden (Bulletin of Environmental Contamination and Toxicology, 2004)

Postindustrial enhancement of aragonite undersaturation in the upper tropical andsubtropical Atlantic Ocean: The role of fossil fuel CO 2 - Sook‐Nye Chung; Geun‐Ha Park; Kitack Lee; Robert M. Key; Frank J. Millero; Richard A. Feely; Christopher L. Sabine; Paul G. Falkowski (Limnology and Oceanography, 2004)
The dissolution of aragonite particles in the ocean primarily depends on the degree of undersaturation of seawater with respect to that mineral. Most of the upper Atlantic Ocean, particularly north of 308S and at depths of less than 2000 m, is supersaturated with respect to aragonite, whereas much of the deep Atlantic is undersaturated. Here we report, for the first time, shallow layers of aragonite‐undersaturated water between 20°S and 15°N in the eastern tropical Atlantic. These layers are centered at 800 m and are surrounded by aragonite‐supersaturated water above and below. This feature most likely results from a combination of chemical and biological processes including the uptake of anthropogenic CO 2 and the oxidation of organic matter falling from the highly productive overlying surface water. Reaction with protons resulting from these processes decreases the carbonate ion concentration and consequently the saturation state of the waters with respect to aragonite. The oceanic uptake of anthropogenic CO 2 during the industrial era has caused a significant increase in the size of the undersaturated layers. Future expansion will likely occur laterally to the west and south, where the degree of supersaturation is low compared to waters to the north. This expansion of the undersaturated layers is a prime example of how human activity during the industrial era has altered the upper ocean chemistry by injecting fossil fuel CO 2 into the ocean.

Dynamical and microphysical characteristics of Arctic clouds using integrated observations collected over SHEBA during the April 1998 FIRE.ACE flights of the Canadian Convair - I. Gultepe; G. A. Isaac; J. Key; J. Intrieri; D. O?C. Starr; K. B. Strawbridge (Meteorology and Atmospheric Physics, 2004)

Acetylcholinesterase Activity in Grass Shrimp and Aqueous Pesticide Levels from South Florida Drainage Canals - P. B. Key; M. H. Fulton; J. A. Harman-Fetcho; L. L. McConnell (Archives of Environmental Contamination and Toxicology, 2003)

Lifestyle determinants of serum insulin-like growth-factor-I (IGF-I), C-peptide and hormone binding protein levels in British women - Naomi E. Allen; Paul N. Appleby; Rudolf Kaaks; Sabina Rinaldi; Gwyneth K. Davey; Timothy J. Key (Cancer Causes & Control, 2003)

Lifestyle and nutritional determinants of bioavailable androgens and related hormones in British men - Naomi E. Allen; Paul N. Appleby; Gwyneth K. Davey; Timothy J. Key (Cancer Causes & Control, 2002)

Circulating levels of sex hormones and their relation to risk factors for breast cancer: a cross-sectional study in 1092 pre- and postmenopausal women (United Kingdom) - Pia K. Verkasalo; Hollie V. Thomas; Paul N. Appleby; Gwyneth K. Davey; Timothy J. Key (Cancer Causes & Control, 2001)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

In situ monitoring of dredged material spoil sites using the oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah; P. P. Maier; N. Hadley; J. W. Daugomah; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

Primary irritant contact dermatitis from synthetic pyrethroid insecticide exposure - Stephen A. Flannigan; Stephen B. Tucker; Marcus M. Key; Charles E. Ross; Edward J. Fairchild; Barbara A. Grimes; Ronald B. Harrist (Archives of Toxicology, 1985)

Basic nuclear proteins in the Omycete fungus Achlya bisexualis - P. A. Horgen; R. T. Nagao; L. S. Y. Chia; J. L. Key (Archives of Microbiology, 1973)